Effect Of Feeding Polyherbal Galactogogue On Milk Yield And Quality In Lactating Crossbred Cows - Jopulkar, P.R.; Dalvi, S.H.; Kapale, P.M.; Ambade, R.B.; Badgujar, S.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Galactagogues are believed to assist in the initiation, maintenance or augmentation of milk production. Twelve crossbred lactating cows at their peak yield of lactation and were in the declining stage of milk production (90-120 days after parturition) were selected and randomly allotted to treatment and control group with six cows in each group. The cows in the treatment group were given 20 gms of polyherbal formulation, daily mixed with feed for a period of 30 days. The results of the present study revealed that the milk production in the cows fed with the polyherbal formulation was increased steadily than that of the control cows. The serum biochemical profile was within the normal range, before, during as well as after the treatment period indicative of normal health status of experimental animals.
Keywords: Polyherbal; Galactagogues; Lactation; Cows